Genetic divergence and its implication in breeding of desired plant type in okra (Abelmoschus esculentus) - SANWAL, S K; SINGH, B; VERMA, SHIV SHANKAR (The Indian Journal of Agricultural Sciences, 2012)
Sixty-seven germplasm lines of okra [Abelmoschus esculentus (L.) Moench] of diverse eco-geographical origin were undertaken in present investigation to determine the genetic divergence following multivariate and canonical analysis for fruit yield and its eight component traits. The 67 genotypes were grouped into five clusters depending upon the genetic architecture of genotypes and characters uniformity and confirmed by canonical analysis. Eighty- nine per cent of total genotypes (60/67) were grouped in two clusters (I, II), while apparent diversity was noticed for 11% genotypes (7/67) that diverged into three clusters (III, IV and V). The maximum intercluster distance was noticed between IV and V (23.38), followed by III and V (21.46), I and V (16.84). The cluster IV was very unique having genotypes of high mean values for most of the component traits. Considering high mean and inter cluster distance breeding plan has been discussed to select desirable plant types.